An evaluation of the effective of intergovernmental relations in local government service delivery : the case study on Thabazimbi Local Municipality - Sithole, Thapelo Florah (My University, 2021)
The study investigated the effectiveness of intergovernmental relations in improving service delivery in the Thabazimbi Local Municipality. Literature argue that despite the relationship between the three spheres of government, Intergovernmental Relations (IGR) does not always promote the constitutional objectives of cooperative governance which impacts on how socio-economic rights such as the provision of adequate housing are implemented. The study was conducted under the premise of quantitative methodology. A purposive sample of 42 respondents was used representing different department/sections/subsections of the Municipality, namely; Office of the Mayor, Office of the Municipal Manager, Chief Financial Officer, Town Planning and Economic Planning, and Cooperate Office. The outcome pointed out that the majority of participants agreed that the IGR framework and other legislation governing the IGR process to enhance service delivery were not fully known and understood to them. The results of the study revealed that there are no structures or forums in place to promote and facilitate intergovernmental relations and provide for appropriate mechanisms to ensure an improved service delivery. Some of the recommendations of the study include appointment of the IGR practitioner, that the TLM should embark on community programmes to inform people on the importance of IGR in developing the Municipality.
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Intergovernmental relations; Service delivery; Thabazimbi Local Municipality; Intergovernmental fiscal relations -- South Africa; Administrative and political divisions; Local government -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo